Effectiveness of Educational Program Based on Planned Behavior Theory on Decreasing Intention of Hookah and Tobacco Supply among the Handlers of Public Places and Food Centers in Arak City - Saeed Bashirian; Hassan Mahmoodi; Majid Barati; Younes Mohammadi (Journal of Education and Community Health)
Aims: Planning to reduce the production and supply of hookah and tobacco can be a positive step to reducing the hookah and tobacco consumption in the community. The aim of the present study was to determine the effectiveness of educational programs on decreasing intention of hookah and tobacco supply among the handlers of public places and food centers in Arak city, Iran based on the theory of planned behavior. Materials & Methods: This research is a quasi-experimental study with the pretest-posttest method and the control group. The present research was carried out among 102 handlers of public places and food centers of Arak city, Iran in 2017 which randomly selected and divided into two experimental (n=51) and control groups (n=51). Data were collected using a questionnaire, including the constructs of the planned behavior theory and demographic variables. The intervention program consisted of 4 sessions that were applied to the experimental group during one month. Both groups were followed for two months after the intervention. Data were analyzed using SPSS 16 software through the chi-square test, independent t-test, paired t-test and McNemar test. Findings: After the educational intervention, significant differences were observed in the changes of attitude constructs, subjective norms, perceived behavioral control and behavioral intention between the experimental and control groups in the pretest-posttest steps (p<0.001). Also, the educational intervention resulted in a 25.1% decrease in the intention of hookah and tobacco supply among the experimental group. Conclusion: The educational interventions based on the theory of planned behavior is effective to reduce the supply of hookah and tobacco among the handlers of public places and food centers.